2016
DOI: 10.1186/s40066-016-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition education on the knowledge scores of urban households with home gardens in Morogoro, Tanzania

Abstract: Background: Home gardens are an old agricultural practice playing a key role in household food security and diversity. Proximity of gardens to the home facilitates easy access to food and reduces household expenditure. Home gardens combined with nutrition education could improve household diets both quantitatively and qualitatively. The objective of this study was to assess the effect of a nutrition education intervention on families with home gardens in Morogoro, Tanzania. Methods:Two cross-sectional nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
2
9
3
1
Order By: Relevance
“…Education is likely to have an impact on the household’s nutritional knowledge and skills to conceptualize and use nutritional promotional messages, which consequently contribute to better dietary diversity[ 38 ]. A previous study in Morogoro in Tanzania reported that households who were provided with nutritional education improved the quality of their household diets[ 39 ]. Households headed by women significantly had higher household dietary diversity scores.…”
Section: Discussionmentioning
confidence: 99%
“…Education is likely to have an impact on the household’s nutritional knowledge and skills to conceptualize and use nutritional promotional messages, which consequently contribute to better dietary diversity[ 38 ]. A previous study in Morogoro in Tanzania reported that households who were provided with nutritional education improved the quality of their household diets[ 39 ]. Households headed by women significantly had higher household dietary diversity scores.…”
Section: Discussionmentioning
confidence: 99%
“…This con rms ndings from similar programs in other regional countries designed to empower communities toward improved agricultural practices 28 . Other opportunities to support empowerment identi ed through the ndings include the potential for KGs to improve food security while facilitating easier access to food, reducing household expenditure, and improving household diets 29 , including food sovereignty and the localization of food systems 30 through more integrated, holistic approaches. 31 This study found limited diversity in food products in the Province.…”
Section: Discussionmentioning
confidence: 99%
“…Different materials were reviewed, these included various publications related to the development and implementation of nutrition education programs, previous nutrition education packages and workshop documentations that have discussed or reviewed nutrition education programs [6,17,18,20,22,29]. The purpose of the review was to identify existing nutrition education materials and gaps.…”
Section: Designing Of Nutrition Education Training Packagementioning
confidence: 99%
“…Studies have shown that poor knowledge related to food consumption may affect dietary practices and suggest the need for behavioural change in the community [7,8,18,19,20]. While several studies regarding the positive impact of nutrition education on behaviour/change exist in Tanzania;the focus has been on the child feeding and nutrition status [20][21][22][23][24][25]. Effect of nutrition education on overall household dietary practices is not given much attention especially in rural parts of the country where the burden of malnutrition is high.…”
Section: Introductionmentioning
confidence: 99%